GEMA online journal of language studies.
Publishes works on literature, with an emphasis on postcolonial and Asian literature in English, linguistics, teaching English as a foreign language, teaching of other languages, and computer applications in language studies.
Refereed/Peer-reviewed
Papers are published electronically on an on-going basis periodically. Selected papers will be published on demand in a hard copy book form.
Keywords: Language and languages -- Study and teaching -- Periodicals.; Linguistics -- Periodicals.; English language -- Study and teaching -- Foreign speakers -- Periodicals.; Oriental literature (English) -- History and criticism -- Periodicals.; English language -- Study and teaching -- Foreign speakers.; Language and languages -- Study and teaching.; Linguistics.; Oriental literature (English); Criticism, interpretation, etc.; Periodicals.